أثر استخدام أدوات الذكاء الاصطناعي وتعلم الآلة ومنصات الحوسبة السحابية على ممارسات المحاسبة: دراسة ميدانية - يوسف، أماني أحمد وهبة (المجلة العلمية للدراسات والبحوث المالية والتجارية: علمية محكمة., 2025)
هدفت الدراسة إلى التعرف على أثر استخدام أدوات الذكاء الاصطناعي وتعلم الألة ومنصات الحوسبة السحابية على ممارسات المحاسبة وكيفية تحسين الكفاءة والدقة عن طريق تحليل أثر استخدامها على الممارسات المحاسبية، استخدمت الدراسة المنهج الاستنباطي، كما استخدمت المنهج الوصفي، وتكونت عينة الدراسة من عدد (75) مفرده من عدد من المحاسبين، أعضاء هيئة تدريس التدريس، واستخدمت الدراسة الاستبيان ومجموعة من أسئلة المقابلة الشخصية لجمع المعلومات اللازمة للدراسة، وتوصلت الدراسة إلى مجموعة من النتائج من أهمها أن تقنيات الذكاء الاصطناعي وتعلم الألة والحوسبة السحابية ساهمت في تحسين كفاءة العمليات المحاسبية من خلال تسريع الإجراءات، تحسين جودة التقارير المالية، وتقليل الأخطاء البشرية. كما عززت الرقابة المالية، التنبؤات المالية الدقيقة، وسرعة الوصول إلى البيانات، مع توفير بيئة تعاونية بين الفرق المالية وزيادة الإنتاجية. ورغم التحديات المرتبطة بتكاليف التطبيق، مثل مقاومة التغيير، نقص التدريب، وعدم توافق الأنظمة، إلا أن المؤسسات ترى أن الفوائد الكبيرة مثل تحسين التحليل المالي، أمان البيانات، وخفض التكاليف تجعل الاستثمار في هذه التقنيات ذا جدوى عالية، وتتميز هذه الدراسة بالأصالة لأنها تقدم تحليلا متكاملا لتأثير ثلاث تقنيات حديثة (الذكاء الاصطناعي، تعلم الألة، الحوسبة السحابية) على ممارسات المحاسبة، مع الاعتماد على دراسة ميدانية توفر بيانات واقعية من المؤسسات. كما أنها تسد فجوة بحثية في الأبحاث السابقة التي غالبا ما ركزت على تأثير كل تقنية على حدة، دون الأخذ في الاعتبار التفاعل المشترك بينها وتأثيره على العمليات المحاسبية. The study aimed to identify the impact of using artificial intelligence and machine learning tools and cloud computing platforms on accounting practices and how to improve efficiency and accuracy by analyzing the impact of their use on accounting practices, the study used the deductive method, and used the descriptive method, and the study sample consisted of (75) single individuals from a number of accountants, faculty members, and the study used the questionnaire and a set of interview questions to collect the necessary information for the study, and the study reached a set of results, the most important of which are that artificial intelligence, machine learning and cloud computing techniques contributed to improving financial control, accurate financial forecasting, and speed of access to data, while providing a collaborative environment for financial teams and increasing productivity. financial control, accurate financial forecasts, fast access to data, a collaborative environment between finance teams, and increased productivity. despite the challenges associated with implementation costs, such as resistance to change, lack of training, and incompatible systems, organizations believe that the significant benefits such as improved financial analysis, data security, and reduced costs make investing in these technologies highly worthwhile. this study is original because it provides an integrated analysis of the impact of three modern technologies (AI, machine learning, and cloud computing) on accounting practices, relying on a field study that provides real-world data from organizations. it also fills a research gap in previous research that often focused on the impact of each technology individually, without considering the interaction between them and its impact on accounting processes.